Evaluation and Improvement of Diesel Cut from Tawke Crude Oil Wells, Zakho - Naman, Salah A.; Maher, K. A.; Simo, Sherwan M. (Science Journal of University of Zakho, 2017)
The straight run diesel cuts of crude oil from T-8 and T-16 Tawke well-Zakho have been examined (qualitative and quantitative). Physical properties such as (density, API, viscosity, cloud point, flash point, water content, sulfur content…. etc.) of this crude oil and diesel product have been measured according to the ASTM method. To improve chemical constituents of these crude oils and increasing the diesel distillation volume cuts by using three types of local clays, X-Ray fluorescence spectroscopy analysis of these clays have been done, a series experiments have been done at a different percentage of local clays and different time of reflux for Tawke wells T-8 and T-16 crude oil. These experiments were performed, in order to optimize the best clay and percentage, as well as finding the suitable reflux time to enhance the volume of the fraction at (200-320) °C. The figures have been plotted to find the optimum percentage weight for each clay, time of reflux, and temperatures. The change in chemical constitutes of these crude oils have been monitored by gas chromatography and tabulated in tables.
Keywords: Tawke wells Number 8 and 16 (T-8) and T-16; Clay; Diesel cut; Crude oil